2022
DOI: 10.1021/acsomega.1c06565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Mechanism of Punicalagin in the Treatment of Alzheimer’s Disease by Computer-Aided Drug Research Technology

Abstract: The objective of this work is to explore the effect and potential mechanism of Punicalagin (Pun) in managing Alzheimer’s disease (AD) based on computer-aided drug technology. The following methods were used: the intersection genes of Pun and AD were retrieved from the database and subjected to PPI analysis, GO, and KEGG enrichment analyses. Preliminary verification was performed by molecular docking, molecular dynamics (MD) simulation, and combined free energy calculation. The motor coordination and balance ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The majority of bioactive compounds found in pomegranate, namely phytobiotics, flavonoids and anthocyanins, are from its peel. These substances possess therapeutic properties, including anti-inflammatory, antioxidant, hypoglycemic and antimicrobial effects (Grabež et al, 2020;Lansky & Newman, 2007;Saeed et al, 2018;Xu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of bioactive compounds found in pomegranate, namely phytobiotics, flavonoids and anthocyanins, are from its peel. These substances possess therapeutic properties, including anti-inflammatory, antioxidant, hypoglycemic and antimicrobial effects (Grabež et al, 2020;Lansky & Newman, 2007;Saeed et al, 2018;Xu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, the toxicity profile of punicalagin still largely remains to be studied as few studies reported nephrotoxicity and liver toxicity exerted by punicalagin while other studies reported a lack of any toxic effect by the molecule Cerdá, Llorach, et al, 2003). Studies suggest the effective dose of punicalagin ranges from 12 to 50 mg/kg oral treatment on a daily basis (Xu et al, 2022) et al, 2022). Sesamol was also found to potentially inhibit Aβ aggregations, suppress neuroinflammation, reduce neuronal and synaptic damage and improve memory and cognition in AD mice (Liu et al, 2021).…”
Section: Plant-derived Polyphenolsmentioning
confidence: 99%
“…Punicalagin is a phenolic compound belonging to the group ellagitannin and is one of the active components of pomegranate Punica granatum . Although possessing low bioavailability (Cerdá, Cerón, et al, 2003; Cerdá, Llorach, et al, 2003; Venusova et al, 2021), the neuroprotective efficacies of punicalagin have been reported in AD and PD studies (Rojanathammanee et al, 2013; Xu et al, 2022). However, the toxicity profile of punicalagin still largely remains to be studied as few studies reported nephrotoxicity and liver toxicity exerted by punicalagin while other studies reported a lack of any toxic effect by the molecule (Cerdá, Cerón, et al, 2003; Cerdá, Llorach, et al, 2003).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%
See 2 more Smart Citations